FRI0322 Rationale for the atacicept dose for a phase iii study in patients with highly active and auto-antibody positive sle. (12th June 2018) - Shen, J.; Papasouliotis, O.; Samy, E.; Haselmayer, P.; Chang, P.; Ona, V.; Kao, A.
Abstract : Background: Atacicept targets the B-cell stimulating factors BLyS and APRIL, and is currently in clinical development for the treatment of patients (pts) with active, auto-antibody positive SLE. Objectives: Here, we evaluated integrated nonclinical, clinical and exposure-response (E-R) data from atacicept studies to determine an appropriate atacicept dose for a Phase (P) III study in SLE pts with high disease activity (HDA). Methods: Nonclinical efficacy and pharmacokinetic (PK)/pharmacodynamic data for atacicept were obtained from two murine models: An F1 hybrid NZBWF1/J spontaneous SLE model (given mouse Fc-protein control or mouse TACI-Fc 5 mg/kg intraperitoneal [IP] three times per week) and a 4-Hydroxy-3-nitrophenylacetyl-Keyhole Limpet Haemocyanin (NP-KLH) vaccinated C57BL/6 model to assess immunomodulation (given control protein 10 mg/kg or atacicept 1, 3 or 10 mg/kg IP every third day). Clinical PK, efficacy, safety and E-R data were obtained from a PI PK study in healthy participants (Study 022; single dose atacicept: 25, 75 or 150 mg) and two PII studies in pts with autoantibody-positive SLE (APRIL-SLE [EudraCT 2007–003698–13] and ADDRESS II [EudraCT 2013–002773–21]; randomization [1:1:1] to once weekly [QW] subcutaneous [SC] injections of atacicept [75 or 150 mg] or placebo [PBO]). In APRIL-SLE, the primary endpoint was the proportion of pts with BILAG A/B flare over 52 weeks. In ADDRESS II, the primary endpoint was SRI-4 response at Week 24. SRI-6 response was analysed post-hoc in pts with HDA (SLEDAI-2K≥10) at Screening. A population PK model was established using data from the PI and PII studies. Population PK model-derived exposure vs probability of clinical response (BILAG A/B flare, SRI-4, SRI-6) was assessed, and an exploratory analysis of exposure vs safety performed. Results: TACI-Fc 5 mg/kg prevented proteinuria development and glomerular damage in the F1 hybrid NZBWF1/J spontaneous SLE model. Anti-KLH IgG decreased markedly in atacicept-treated NP-KLH vaccinated mice (>50% reduction vs control protein at all doses), with mean atacicept serum trough concentrations (Cmin ) of 2.3 µg/mL (1 mg/kg), 5 µg/mL (3 mg/kg) and 8.5 µg/mL (10 mg/kg). In post-hoc analyses of the proportion of pts with BILAG A/B flare and time to flare in APRIL-SLE, and SRI-4 and SRI-6 response in SLE pts with HDA in ADDRESS II, treatment with atacicept 150 mg QW demonstrated greater clinical response vs PBO. In both studies, atacicept E-R relationships based on population PK-derived exposure were observed. For maximal flare reduction, an atacicept exposure of AUC ≥1 mg*hr/mL was identified. This exposure was more achievable with 150 than 75 mg (60% vs 15% probability) and corresponded to an atacicept Cmin of 5 µg/mL, which was similar to the Cmin values observed in the NP-KLH vaccinated mouse model. Both atacicept 150 and 75 mg had acceptable safety profiles in SLE pts, with no apparent E-R relationship observed for serious infections. Conclusions: Integrated nonclinical, clinical and E-R data demonstrate an acceptable benefit-risk profile for atacicept in SLE pts with HDA and support the selection of the 150 mg QW dose for a PIII study. Disclosure of Interest: J. Shen Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), O. Papasouliotis Employee of: Merck Institute for Pharmacometrics, Lausanne, Switzerland (an affiliate of Merck KGaA, Darmstadt, Germany), E. Samy Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), P. Haselmayer Employee of: Merck KGaA, P. Chang Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), V. Ona Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), A. Kao Employee of: EMD Serono Research and Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany)